2018
DOI: 10.3390/ma11040575
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-Silica Nanocomposites of High Reinforcing Content with Fungi Decay Resistance by One-Pot Synthesis

Abstract: Hybrid bionanocomposites based on cellulose matrix, with silica nanoparticles as reinforcers, were prepared by one-pot synthesis of cellulose surface modified by solvent exchange method to keep the biopolymer net void for hosting inorganic nanoparticles. Neither expensive inorganic-particle precursors nor crosslinker agents or catalysts were used for effective dispersion of reinforcer concentration up to 50 wt %. Scanning electron microscopy of the nanocomposites shows homogeneous dispersion of reinforcers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Comparing the results of this work with those obtained in our previous work of hybrid bionanocomposites synthesized by only one step, using only pristine raw materials of cellulose and silica we observed that after 500 °C degradation the composites of solvent exchange treated matrix retained about 12 wt% more than the composite of no solvent exchange treated matrix indicating that the matrix is better stabilized by the reinforcer particles when it is solvent exchange treated delivering higher thermal stabilization to such composites than the composites of just pristine cellulose matrix . The results of this work indicate that even when the raw materials used are obtained from secondary raw resources the synthesized materials performance is very similar to that of the pristine raw resources composites prepared by a very similar way that is low energy demanding and requires just one‐step synthesis.…”
Section: Resultssupporting
confidence: 74%
“…Comparing the results of this work with those obtained in our previous work of hybrid bionanocomposites synthesized by only one step, using only pristine raw materials of cellulose and silica we observed that after 500 °C degradation the composites of solvent exchange treated matrix retained about 12 wt% more than the composite of no solvent exchange treated matrix indicating that the matrix is better stabilized by the reinforcer particles when it is solvent exchange treated delivering higher thermal stabilization to such composites than the composites of just pristine cellulose matrix . The results of this work indicate that even when the raw materials used are obtained from secondary raw resources the synthesized materials performance is very similar to that of the pristine raw resources composites prepared by a very similar way that is low energy demanding and requires just one‐step synthesis.…”
Section: Resultssupporting
confidence: 74%
“…Before this method, it was impossible to incorporate cellulose particles into nonpolar polymers without the use of surface modification or surfactants [15,16]. Previously, we reported that the method application for the synthesis of cellulose-based hybrid nanocomposites with high content of silica nanoparticles showing inhibition growth of Trametes versicolor fungi [17].…”
Section: Methodsmentioning
confidence: 99%
“…[30] Silica is ecofriendly in the sense of its abundance, and cellulose-silica composites have been studied for protection against fungal decomposition, gas separation, etc. [31][32][33][34][35][36] Cellulose and its derivatives have also been used in combination with silica particles for aerogels, desalination membranes, membranes for oil water separation, films for passive radiative cooling, filters for cigarette smoke, thermal insulation etc. [37][38][39][40][41][42][43] A straightforward process to facilitate infiltration and achieve homogenous distribution of silica into cellulose can enhance the processibility and scalability for fabrication of these functional materials.…”
Section: Introductionmentioning
confidence: 99%